Influence of static stretching on hamstring flexibility in healthy young adults: Systematic review and meta-analysis. (17th August 2016) - Medeiros, Diulian M.; Cini, Anelize; Sbruzzi, Graciele; Lima, Cláudia S.
ABSTRACT: The aim of the current study was to investigate the influence of static stretching on hamstring flexibility in healthy young adults by means of systematic review and meta-analysis. The search strategy included MEDLINE, PEDro, Cochrane CENTRAL, EMBASE, LILACS, and manual search from inception to June 2015. Randomized and controlled clinical trials studies that have compared static stretching to control group, and evaluated range of motion (ROM), were included. On the other hand, studies that have worked with special population such as children, elderly people, athletes, and people with any dysfunction/disease were excluded, as well as articles that have used contralateral leg as control group or have not performed static stretching. The meta-analysis was divided according to three types of tests. Nineteen studies were included out of the 813 articles identified. In all tests, the results favored static stretching compared to control group: passive straight leg raise (12.04; 95% CI: 9.61 to 14.47), passive knee extension test (8.58; 95% CI: 6.31 to 10.84), and active knee extension test (8.35; 95% CI: 5.15 to 11.55). In conclusion, static stretching was effective in increasing hamstring flexibility in healthy young adults.